“No Somos Amargados ni Fracasados”: Collective Play, Public Parks, and Loving Community among Latino Men - Teresa Irene Gonzales; Lillian Wynne Platten (Sociological Perspectives, 2026)
Urban studies highlight the importance of public parks in fostering community, rest, and civic engagement. Yet for low-income and Latinx/e populations, public spaces that support leisure and community are often scarce or stigmatized as unsafe. To better understand the relationship between public space and social belonging, this paper analyzes the significance of public parks in the lives of Dominican and Puerto Rican men in Lawrence, Massachusetts. Drawing on ethnographic and interview data collected over nearly four years, we argue that parks in Lawrence serve as temporal sites for Latinx pla(y)making. This process increases feelings of belonging, transforms the local environment in culturally relevant ways, and, through collective play, affirms cultural heritage while generating loving community and belonging rooted in Caribbean and Latinx/e saberes. These embodied practices—which are too often viewed as unruly by dominant culture—work in opposition to negative “controlling images” and dominant narratives of degradation.